The relationship between budget deficit and external deficit : the case of Portugal - Coelho, José Carlos (2020)
This paper makes an empirical analysis applied to Portugal between 1999 and 2016 which investigates the existence of a causal relationship between the budget balance (overall and primary) and the external balance (goods and services and current). Using Granger Causality Test (1969) and the Toda-Yamamoto Methodology (1995), we conclude that there is causality between the overall budget balance and the current external balance and between the primary budget balance and the current external balance, which provides support to the Twin Deficits Hypothesis. We also found some evidence to verify the Current Account Targeting Hypothesis, which points to the possibility of bi-directional causality between the budget deficit and the external deficit in Portugal.